"The world food crisis is not a fad": The More-with-Less Cookbook and Protestant Environmental Spirituality. Issue 2 (2019) - Rose, Kevin Stewart
ABSTRACT: This article examines the spirituality reflected in the 1976 cookbook More-with-Less . Written by a former Mennonite missionary hoping to provide religious households with a practical way to respond to world hunger, the cookbook's message of a simple diet that could transform users' influence on the world is an early example of the religious environmentalism that has grown increasingly popular among middle-class American Protestants in the last several decades. By examining its historical context, narrating its genesis, and critically assessing the spirituality it recommended, this article argues that the cookbook provides a useful window into Protestant environmental spirituality, its version of which allowed practitioners to maintain traditional institutional relationships and conceptions of the divine while cultivating the individuated religiosity increasingly sought after in modern culture. Emerging in the institutional overlap of traditional religious organizations and the putatively secular formations of mass media, globalization, and consumer culture, the cookbook leveraged the incipient emphasis on lifestyle choices within consumer culture to craft an individuated response to a vision of the world in permanent crisis. More-with-Less and the Protestant environmental spirituality it represents shed light on current scholarly debates about the form religion takes within modern contexts of secularity, especially when religious practitioners seek adaptations that can maintain traditional theological and organizational commitments.